Comparison of Residual Cancer Burden, American Joint Committee on Cancer staging and Pathologic Complete Response in Breast Cancer after Neoadjuvant Chemotherapy: Results from the I-SPY 1 TRIAL (CALGB 150007/150012; ACRIN 6657) - Campbell, Jeffrey I. (Breast Cancer Res Treat, 2017)
PURPOSE: Several pathologic staging systems characterize residual tumor in patients undergoing neoadjuvant chemotherapy for breast cancer. Pathologic complete response (pCR) is now accepted by the Food and Drug Administration as an endpoint for granting accelerated drug approval. Two other systems of post-neoadjuvant pathologic tumor staging—Residual Cancer Burden (RCB) and the American Joint Committee on Cancer post-neoadjuvant therapy staging system (yAJCC)—have been developed to characterize residual tumors when patients do not achieve pCR. The optimal system, and the ways in which these systems complement each other, have not been fully determined. METHODS: Using data from the I-SPY 1 TRIAL, we compared pCR, RCB and yAJCC as predictors of early recurrence-free survival (RFS) to identify ways to improve post-neoadjuvant pathologic evaluation. RESULTS: Among 162 patients assessed, pCR identified patients at lowest risk of recurrence, while RCB and yAJCC identified patients at highest risk. Hormone-receptor (HR) and HER2 subtypes further improved risk prediction. Recursive partitioning indicated that triple negative or HER2+ patients with yAJCC III or RCB 3 have the highest recurrence risk, with an RFS of 27%. Our analysis also highlighted discrepancies between RCB and yAJCC stratification: 31% of patients had discrepant RCB and yAJCC scores. We identified differential treatment of lymph node involvement and tumor cellularity as drivers of these discrepancies. CONCLUSIONS: These data indicate that there is benefit to reporting both RCB and yAJCC for patients in order to identify those at highest risk of relapse.